2012
DOI: 10.4049/jimmunol.1101980
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils Preserve Parasitic Nematode Larvae by Regulating Local Immunity

Abstract: Eosinophils play important roles in regulation of cellular responses under conditions of homeostasis or infection. Intestinal infection with the parasitic nematode, Trichinella spiralis induces a pronounced eosinophilia that coincides with establishment of larval stages in skeletal muscle. We have shown previously that in mouse strains in which the eosinophil lineage is ablated, large numbers of T. spiralis larvae are killed by nitric oxide, implicating the eosinophil as an immune regulator. In this report, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
113
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 54 publications
(70 reference statements)
7
113
0
Order By: Relevance
“…The resulting excessive host inflammatory responses led to the death of the resident parasite and, in turn, significant muscle pathology/necrosis. The failure of nurse cells to thrive in eosinophil-deficient mice was rescued by intravenous transfer of eosinophils into the mice, 26 demonstrating a direct role for eosinophils in aiding helminth survival while at the same time dampening the inflammatory response of the host. The mechanisms of this eosinophil-mediated macrophage regulation remain to be defined, yet studies by Stolarski et al that demonstrated eosinophil release of IL-4 and IL-13 polarized macrophage toward an M2 phenotype suggest a mechanism by which eosinophils directly modulate local Th2 polarization conditions to protect the resident parasite.…”
Section: Roles Of Eosinophils In Health and Disease 3883mentioning
confidence: 90%
See 2 more Smart Citations
“…The resulting excessive host inflammatory responses led to the death of the resident parasite and, in turn, significant muscle pathology/necrosis. The failure of nurse cells to thrive in eosinophil-deficient mice was rescued by intravenous transfer of eosinophils into the mice, 26 demonstrating a direct role for eosinophils in aiding helminth survival while at the same time dampening the inflammatory response of the host. The mechanisms of this eosinophil-mediated macrophage regulation remain to be defined, yet studies by Stolarski et al that demonstrated eosinophil release of IL-4 and IL-13 polarized macrophage toward an M2 phenotype suggest a mechanism by which eosinophils directly modulate local Th2 polarization conditions to protect the resident parasite.…”
Section: Roles Of Eosinophils In Health and Disease 3883mentioning
confidence: 90%
“…Recent studies by Gebreselassie et al 26 and Fabre et al 27 in the mouse may have provided a solution to this quandary, suggesting a unique role for eosinophils not in parasite killing but instead for parasite survival. Specifically, Trichinella spiralis has a 2-stage life cycle whereby newborn larvae convert a muscle cell into a nurse cell for the developing parasite.…”
Section: Roles Of Eosinophils In Health and Disease 3883mentioning
confidence: 99%
See 1 more Smart Citation
“…he parasitic nematode Trichinella spiralis induces potent Th2 responses that both clear intestinal infections and regulate immunity in extraintestinal sites (1)(2)(3)(4)(5). The innate cellular and molecular drivers of Th2 immunity appear to vary among nematode infections, and the identification of mechanisms that initiate Th2 responses continues to be an area of active research (reviewed in reference 6).…”
mentioning
confidence: 99%
“…Thus, the benefit to the host of its own survival is attached to the cost of continued shedding of eggs and perpetuation of the parasite in the environment and host population. In recent years, additional examples of Th2 responses that support parasitic worm survival have been described for other tissue-dwelling worms (15)(16)(17). In contrast, effective clearance of worms that colonize the intestine has been shown in several models to be mediated by various Th2-dependent mechanisms (18).…”
Section: Costs and Benefits Of Immunity To Worm Infectionmentioning
confidence: 99%